Implementation research and Asian American/Pacific Islander health - Jenny Hsin-Chun Tsai; Shin-Ping Tu; Nancy A. Perrin; Erica S. Breslau (JMIR Publications, 2016)
Numerous barriers prevent the translation of research into practice, especially in settings with diverse populations. Nurses are in contact with diverse populations across settings and can be an important influence to further implementation research. This paper describes conceptual approaches and methodological issues pertinent to implementation research and implications for Asian American/Pacific Islander (AAPI) health research. The authors discussed the values of using theory to guide implementation research, levels of theory that are commonly used in interventions, and decisions for theory selection. They also articulated the shortcoming of randomized controlled trials, the gold standard for testing efficacy of interventions, and present quasi-experimental designs as a plausible alternative to randomized controlled trials when research is conducted in real-world settings. They examined three types of quasi-experimental designs, the unit of analysis, the choice of dependent variables, and measurement issues that influence whether research findings and evidence-based interventions are successfully translated into practice. Practicing nurses who are familiar with the AAPI population, as well as nurse researchers who have expertise in AAPI health can play critical roles in shaping future implementation research to advance AAPI health. Nurses can provide practice-based evidence for refining evidence-supported interventions for diverse, real-world settings and theory-based interventions that are socioculturally appropriate for AAPIs. Interdisciplinary, practice-based research networks that bring multiple agencies, organizations, communities, and academic institutions together can be a mechanism for advancing implementation research for AAPI health.